Keefektifan penggunaan metode Course Review Horay dalam pembelajaran keterampilan menyimak bahasa Jerman - Lestari, Nanda; Mulyati, Retna Endah Sri (Journal of Culture, Literature and Foreign Language Teaching, 2025)
This research aimed to determine (1) the difference in students' learning achievement between those taught with the Course Review Horay method and conventional methods, (2) the effectiveness of using the Course Review Horay method in learning German listening skills. This research is a quasi-experiment. The research was conducted at SMA Negeri 1 Sedayu Bantul with XI MIPA 3 class as the experimental class and XI MIPA 5 as the control class. The research data were obtained from the pre-test and post-test of German listening skills. T-test with significance level of 0.05 was used for data analysis. The data obtained t_count value of 3.033 is greater than t_table of 1.668 at 0.05 level of significance. The data shows that there is a difference in learning achievement between the experimental class and the control class. The mean post-test of the experimental class of 80.29 was greater than the control class of 74.97 with an effectiveness weight of 8.61%. It can be concluded that the use of Course Review Horay method is effective in learning German listening skills of XI grade students of SMA Negeri 1 Sedayu Bantul.